KORESPONDENSI FONEMIS BAHASA KONJO DAN BAHASA SELAYAR (Phonemic Correspondence of Konjo and Selayar Languages) - Musayyedah Husain (SAWERIGADING, 2015)
This paper discussed about phonemic correspondence Konjo language and Selayar language using historical-comparative linguistic approach. This study was conducted by using a similar form and meaning as a reflection of the same historical heritage. The research objective is to find patterns of phonemic correspondence of both languages through phonemic recurrence, co-occurence, or analogy. The method used phonemic correspondence analysis between Konjo language and Selayar language with data source is 200 gloss words compared in both languages. The results showed that changes in sound between derivedlanguages in reflecting the sounds contained in proto-languages that lead to different languages or dialects, there are regular and irregular (sporadic). It is dependent of the law of sound changes arising from Konjo language and Selayar language. The results of this paper found some phonemic correspondence from 200 gloss which are comparable, found 48 glosses that have shape, sound, and meaning exactly same. Between Konjo language and Selayar language showed phonemic correspondence which appears regularly. Formula phoneme correspondences are found in both languages there are six sets phonemic correspondence i.e. /Ԑ ~ e / - # ; o ~ Ԑ / - # ; k ~ r / # - ; Ø ~ w / v – v ; l: l ~ ll / v – v; k: k ~ kk / v – v.